PENGARUH PENGGUNAAN E-WALLET TERHADAP KONSUMSI DI KALANGAN MAHASISWA/I WILAYAH JAKARTA DAN JAWA BARAT PADA MASA COVID-19 - Anastasia, Benita; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to obtain evidence about the effect of using e-wallets on consumption among students in the Jakarta and West Java areas during the COVID-19 period. The design of this study was made in order to find out whether there is a direct or indirect effect given by the independent variable on the independent variable. This study used simple random sampling and produced a sample of 200 people from 321 people. Furthermore, for testing the is hypothesis, it is done using a simple linear regression method. This research was conducted using the SPSS (Statistical Product and Service Solution) application. The results showed that the use of e-wallet seen from all indicators (practical, security, human error, limits, recording reports and changes) had a significant effect on consumption variables. The implication of this research is that students should be more aware of the use of e-wallet, even though they can consume it effectively and easily. But students must be able to exercise control, and be introspective of the effects that arise after the use.